Immunomodulatory Effects of Oyster Mushroom (Pleurotus sajor-caju) Extract In Balb/c Mice. - Nurul, A. A.; Jonathan, M. A.; Jamaruddin, M. A.; Wan Rosli, W. I. (Research & Reviews, 2014)
Pleurotus sajor-caju (oyster mushroom, PSC) is widely used in culinary due to its various benefits on human health. However, no study has been reported on its immunomodulating properties. Cultivated mushroom powder was used for hot aqueous extraction using Soxhlet technique. The PSC extract was suspended into CMC and prepared into 3 groups: 0.2 g/kg, 1g/kg and 2g/kg. Balb/c mice were orally fed daily for 21 consecutive days. Treatment of mice with various concentrations of PSC showed increased populations of CD3+/CD4+, CD3+/CD8+, CD14+ and CD 19+ cells. Interestingly, PSC-treated mice demonstrated significant increase in CD3+/CD4+ and CD19+ cells. Most importantly, mice treated with PSC showed improved CD4+/CD8+ ratio; which indicated potential immunostimulating activity by PSC. In addition, no physical changes and signs of mortality could be detected from PSC-treated mice. The results suggest that PSC may improve general immune status when consumed consistently as a daily food option.